Iron-containing catalyst, preparation method and application thereof, and method for producing hydrogen through ammonia decomposition

By using a magnesium titanate support and an iron-supported catalyst, the existing ammonia decomposition catalysts are solved, and the efficient and stable ammonia decomposition hydrogen production effect is achieved.

CN119897105AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311410670.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The activity and stability of existing ammonia decomposition catalysts at low temperatures need to be further improved, resulting in a low efficiency of ammonia decomposition and hydrogen production.

Method used

Magnesium titanate is used as a support and the iron-supported catalyst is prepared by the sol-gel method, and the iron content is controlled at 5-20% by weight to improve the activity and stability of the catalyst.

Benefits of technology

The ammonia decomposition conversion rate and reaction space speed are significantly improved at low temperatures, and the catalyst has good stability and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004518074790000161
    Figure BDA0004518074790000161
  • Figure BDA0004518074790000171
    Figure BDA0004518074790000171
Patent Text Reader

Abstract

The invention relates to the field of ammonia decomposition catalyst preparation, and discloses an iron-containing catalyst, a preparation method and application thereof, and a method for producing hydrogen through ammonia decomposition. The invention relates to an iron-containing catalyst. The catalyst comprises a magnesium titanate carrier and an iron element loaded on the magnesium titanate carrier, wherein on the basis of the total weight of the catalyst, the content of iron is 5-20wt% in terms of iron element. The catalyst has relatively high activity, is applied to hydrogen production through ammonia decomposition, and has a relatively high ammonia decomposition conversion rate at a low temperature and a relatively high reaction space velocity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of ammonia decomposition catalysts, and in particular to an iron-containing catalyst and a preparation method and application thereof, as well as a method for producing hydrogen by decomposing ammonia. Background Art

[0002] At present, hydrogen almost comes from the catalytic steam reforming of fossil fuels, which is also the most mature commercial hydrogen production technology. However, the hydrogen extracted by catalytic reforming will be accompanied by impurity gases such as carbon monoxide and carbon dioxide, and cannot be directly used as fuel cell fuel. Therefore, using ammonia as a raw material for carbon-free hydrogen production is an efficient, clean and safe hydrogen production technology. In order to achieve safe and green hydrogen production, it is particularly important to develop catalysts that can efficiently catalyze the decomposition of ammonia. At present, ammonia decomposition catalysts are divided into precious metal catalysts with ruthenium and platinum as active components and non-precious metal catalysts with iron and nickel as active components.

[0003] The high cost and low reserve of precious metals limit their application in large-scale industrialization. Therefore, the core of developing efficient and low-cost ammonia decomposition hydrogen production technology lies in low-cost, high-activity and high-stability non-precious metal catalysts. However, non-precious metal catalysts require more stringent reaction conditions, and the operating temperature is generally higher than 800°C. For this reason, extensive research has been conducted on low-temperature non-precious metal ammonia decomposition catalysts. For example, CN1506299A discloses a nickel-based ammonia decomposition hydrogen-nitrogen mixed gas catalyst, whose main active component is Ni; the carrier is SiO2 or Al2O3; the auxiliary agent is one or more of IA, IIA, IIIB, VIII or rare earth elements; the weight percentage of nickel is 1-40%; the weight percentage of the auxiliary agent component is 0.1-20%. The catalyst is prepared by using SiO2 or Al2O3 as a carrier. Although the catalyst is improved by introducing an additive, ammonia decomposition can be performed at 650°C, which is significantly lower than the reaction temperature of 800°C of industrial catalysts. However, due to the poor dispersion of the additive on the carrier surface, large particles are easily formed, resulting in poor ammonia decomposition activity at low temperatures. CN115646500A discloses a catalyst for hydrogen production by decomposing ammonia, which includes an active metal component, an alkaline earth metal component, a lanthanide metal component and an additive. In this patent application, alkaline earth metal is doped to improve the dispersion of the nickel-based catalyst and reduce the particle size. Compared with the unmodified catalyst, the activity of the catalyst has been improved to a certain extent. Although the reaction temperature is reduced to 550°C, the reaction space velocity is only 6000mL / (g·h), and there is still room for improvement. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the activity and stability of the existing ammonia decomposition catalyst at low temperature need to be further improved, and to provide an iron-containing catalyst and its preparation method and application, as well as a method for producing hydrogen by decomposing ammonia. The catalyst has high activity and is applied to hydrogen production by decomposing ammonia, and has a higher ammonia decomposition conversion rate at low temperature and high reaction space velocity.

[0005] In order to achieve the above object, the present invention provides an iron-containing catalyst on one hand, wherein the catalyst comprises a magnesium titanate carrier and an iron element supported on the magnesium titanate carrier;

[0006] Wherein, based on the total weight of the catalyst, the content of iron is 5-20% by weight in terms of iron element.

[0007] A second aspect of the present invention provides a method for preparing an iron-containing catalyst, the method comprising the following steps:

[0008] S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A;

[0009] S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B;

[0010] S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5;

[0011] S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier;

[0012] S5. Loading the iron element on the magnesium titanate carrier.

[0013] The third aspect of the present invention provides an application of the iron-containing catalyst described in the first aspect or the iron-containing catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.

[0014] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;

[0015] Wherein, the catalyst is the catalyst described in the first aspect or the iron-containing catalyst prepared by the preparation method described in the second aspect.

[0016] Through the above technical solution, the beneficial effects of the present invention include:

[0017] The iron-containing catalyst provided by the present invention adopts the synergistic effect of iron element and magnesium titanate carrier, which is beneficial to improving the catalytic activity of the catalyst; at the same time, the content of iron element is controlled within the range of 5-20 weight%, which is beneficial to enhancing the interaction between the iron active component and the carrier, and effectively weakening the interaction between the iron active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen.

[0018] The catalyst of the present invention adopts non-precious metal raw materials, does not contain precious metals such as Ru, is cheap, has a simple preparation process, good repeatability, and is easy to carry out large-scale production. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides an iron-containing catalyst, the catalyst comprising a magnesium titanate carrier and an iron element supported on the magnesium titanate carrier;

[0021] Wherein, based on the total weight of the catalyst, the content of iron is 5-20% by weight in terms of iron element.

[0022] The inventors of the present invention have found that the use of magnesium titanate as a carrier can adjust the electron transfer capacity between the active components in the catalyst and the carrier, adjust the adsorption and desorption intensity of NH3 on the catalyst surface, promote the transfer of NH3 between the active sites and the carrier, and improve the catalytic activity.

[0023] In the present invention, based on the total weight of the catalyst, the content of iron is 5-20% by weight, preferably 10-20% by weight, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, and any value in the range formed by any two of these values. This preferred embodiment is beneficial to enhancing the interaction between the iron active component and the carrier, and effectively weakening the interaction between the iron active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen.

[0024] The total content of each component of the catalyst of the present invention is 100%.

[0025] The content of active components in the catalyst of the present invention is measured by XRF characterization.

[0026] Preferably, the catalyst does not contain precious metals. This preferred embodiment can save costs.

[0027] A second aspect of the present invention provides a method for preparing an iron-containing catalyst, the method comprising the following steps:

[0028] S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A;

[0029] S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B;

[0030] S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5;

[0031] S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier;

[0032] S5. Loading the iron element on the magnesium titanate carrier.

[0033] The preparation method provided by the present invention first adopts a sol-gel method to prepare a magnesium titanate carrier, and then the iron active component is loaded on the magnesium titanate carrier, and the obtained iron-containing catalyst has higher activity. In the preparation process of the magnesium titanate carrier, the titanium source and the magnesium source are first dissolved in an alcohol-glacial acetic acid mixed solution respectively, and the alcohol and glacial acetic acid are used as solvents to inhibit the hydrolysis of the titanium source and improve the time of gel formation; then the B solution is added to the A solution to mix the two, and the pH of the obtained sol is controlled within the range of 1.5-5, which is conducive to promoting the synergistic effect of the obtained magnesium titanate carrier and the iron element, thereby improving the catalyst activity.

[0034] According to the present invention, preferably, in S1, the mass ratio of the titanium source to the alcohol-glacial acetic acid mixed solution is 1:4-10. This preferred embodiment is conducive to the rapid formation of a uniform sol.

[0035] The present invention has no particular limitation on the type of the titanium source, which can be a conventional choice in the art. Preferably, the titanium source is a water-soluble titanium-containing compound, preferably at least one selected from tetrabutyl titanate, ethyl titanate and isopropyl titanate. The above titanium sources can all be obtained commercially, and are cheap and easy to obtain.

[0036] According to the present invention, preferably, in S2, the mass ratio of the magnesium source to the alcohol-glacial acetic acid mixed solution is 1:4-20. This preferred embodiment is conducive to the rapid formation of a uniform sol.

[0037] The present invention has no particular limitation on the type of magnesium source, which can be a conventional choice in the art. Preferably, the magnesium source is a soluble magnesium salt, preferably at least one selected from magnesium nitrate, magnesium sulfate and magnesium chloride.

[0038] In the present invention, the "soluble" means that the compound can be dissolved in a solvent directly or with the help of a co-solvent.

[0039] The present invention has no particular limitation on the amount of glacial acetic acid used, and the amount is based on obtaining a sol with the following pH.

[0040] According to the present invention, preferably, in the alcohol-glacial acetic acid mixed solutions of S1 and S2, the mass ratio of glacial acetic acid to alcohol is independently 1:0.5-2.

[0041] The alcohol of the present invention is used as a solvent to dissolve the magnesium source and the titanium source. The alcohol of the present invention has a wide selection range and can be a conventional choice in the art. Preferably, the alcohols of S1 and S2 are each independently a C1-C5 alcohol, preferably at least one selected from methanol, ethanol and propanol.

[0042] In the present invention, in S3, the pH of the sol is 1.5-5, preferably 3-5, such as 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and any value in the range formed by any two of these values. This preferred embodiment is further conducive to promoting the synergistic effect of the obtained magnesium titanate support and the active component, thereby improving the activity of the catalyst.

[0043] The chemical formula of magnesium titanate is MgO3Ti. In order to make the reaction of solution A and solution B complete, the molar ratio of titanium to magnesium satisfies the above chemical formula. Preferably, the molar ratio of solution A calculated in terms of titanium element to solution B calculated in terms of magnesium element is 1:1.

[0044] According to a specific embodiment of the present invention, the B solution is added dropwise into the A solution while stirring.

[0045] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to specific circumstances, subject to the B solution and the A solution being mixed uniformly.

[0046] According to the present invention, preferably, the treatment conditions include: a temperature of 30-50°C, preferably 30-40°C, for example, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, and any value in the range formed by any two of these values; a time of 0.5-10h, preferably 0.5-8h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to faster and better formation of sol.

[0047] Preferably, the treatment is carried out under static conditions.

[0048] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art. Preferably, in S4, the drying conditions include: a temperature of 70-100° C. and a time of 8-48 hours.

[0049] According to the present invention, preferably, in S4, the conditions of the first calcination include: a temperature of 600-1000° C. and a time of 2-6 hours.

[0050] According to the present invention, preferably, in S5, the iron element is loaded on the magnesium titanate carrier by a co-precipitation method.

[0051] Further preferably, the coprecipitation method in S5 comprises: mixing an aqueous solution of an iron compound, a suspension containing a magnesium titanate carrier and an alkaline solution to obtain a solid product, and then drying and second calcining the solid product.

[0052] According to the present invention, preferably, the iron-containing compound is used in an amount such that the iron content in the prepared catalyst is 5-20% by weight, preferably 10-20% by weight, calculated as iron element, based on the total weight of the catalyst.

[0053] The present invention has no particular limitation on the order of adding the aqueous solution of the iron-containing compound, the suspension containing the magnesium titanate carrier and the alkaline solution in the above-mentioned mixing process of S5, and they can be added separately or together. In the embodiment of the present invention, it is preferred to add the aqueous solution of the iron-containing compound and the alkaline solution together to the suspension containing the magnesium titanate carrier.

[0054] According to the present invention, preferably, the reaction conditions include: temperature of 40-70°C, time of 3-8h, and pH of 8-10.

[0055] Preferably, the reaction is carried out under stirring conditions.

[0056] The present invention has no particular limitation on the stirring rate, and it can be appropriately selected according to specific circumstances to accelerate the reaction process.

[0057] The present invention has a wide range of selections for the type of the iron-containing compound, which can be a conventional choice in the art. Preferably, the iron-containing compound is selected from at least one of ferric nitrate, ferric sulfate and ferric chloride.

[0058] Preferably, the concentration of the alkaline solution is 0.5-10 mol / L.

[0059] The present invention has a wide range of base types, and can be various bases commonly used in the art. Preferably, the base is an organic base and / or an inorganic base, preferably at least one selected from sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate and ammonia water.

[0060] The present invention has no particular limitation on the amount of the alkaline solution, provided that the pH of the reaction is within the above range.

[0061] Preferably, the method further comprises: filtering and washing the reaction product to obtain a solid product.

[0062] The present invention has no particular limitation on the specific methods of filtering and washing, and the filtering and washing can be performed according to conventional methods in the art.

[0063] Preferably, the preparation of the suspension containing the magnesium titanate carrier comprises: dispersing the magnesium titanate carrier in water, and heating the water to 40-70° C. to obtain the suspension containing the magnesium titanate carrier.

[0064] In the present invention, the magnesium titanate carrier may be dispersed in water by conventional techniques such as stirring or ultrasound to achieve uniform mixing, and the present invention has no particular limitation on this.

[0065] The present invention has no particular limitation on the drying in S5, and the drying can be carried out according to conventional methods in the art, which will not be described in detail herein.

[0066] The second calcination is not particularly limited in the present invention and can be performed according to conventional methods in the art. Preferably, the conditions of the second calcination include: a temperature of 550-780° C. and a time of 2-5 hours.

[0067] According to the present invention, preferably, the method further comprises: reducing the product of the second calcination to obtain the catalyst.

[0068] According to the present invention, preferably, the reduction conditions include: temperature of 600-800° C. and time of 1-3 h.

[0069] According to the present invention, preferably, the reduction is carried out in a reducing gas, the reducing gas comprises hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%.

[0070] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, adopting or not adopting. Specifically, an inert gas may or may not be added in the reduction step of the present invention.

[0071] According to the present invention, preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon.

[0072] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0073] The third aspect of the present invention provides an application of the iron-containing catalyst described in the first aspect or the iron-containing catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.

[0074] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;

[0075] Wherein, the catalyst is the catalyst described in the first aspect or the iron-containing catalyst prepared by the preparation method described in the second aspect.

[0076] In the prior art, the temperature of the ammonia decomposition reaction using a catalyst without precious metals is generally higher than 550° C. However, the catalyst of the present invention still has a high ammonia decomposition activity at low temperatures, and the ammonia decomposition temperature can be as low as 550° C. Moreover, the ammonia decomposition reaction of the present invention can be carried out at a relatively high space velocity, and the ammonia decomposition activity is still maintained at a relatively high level after a long-term evaluation experiment, indicating that the catalyst of the present invention has good stability.

[0077] According to the present invention, preferably, the conditions for decomposing ammonia include: a temperature of 550-650° C. and a volume space velocity of 5000-20000 mL / (g·h).

[0078] The present invention will be described in detail below through examples.

[0079] In the following examples, the ammonia decomposition conversion rate formula is as follows:

[0080] Ammonia decomposition conversion rate = (raw material ammonia content - product ammonia content) / raw material ammonia content × 100%.

[0081] Example 1

[0082] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0083] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 107.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0084] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 30.8 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0085] 4) Add the above solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0086] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0087] 6) Ultrasonic dispersion of 9.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 2.2 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 5% by weight in terms of iron element.

[0088] Example 2

[0089] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0090] 2) Weigh 25.5 g of tetrabutyl titanate and disperse it in 101.9 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0091] 3) Weigh 7.3 g of magnesium nitrate and disperse it in 29.2 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0092] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0093] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0094] 6) Ultrasonic dispersion of 9 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 4.3 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the obtained metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 10% by weight in terms of iron element.

[0095] Example 3

[0096] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 2:3.

[0097] 2) Weigh 24.1 g of tetrabutyl titanate and disperse it in 96.3 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0098] 3) Weigh 4.4 g of magnesium chloride and disperse it in 17.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0099] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 4.

[0100] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 4 h to obtain a magnesium titanate carrier.

[0101] 6) Ultrasonic dispersion of 8.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 6.5 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2.0 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 600°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 30% at 800°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 15% by weight in terms of iron element.

[0102] Example 4

[0103] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0104] 2) Weigh 22.7 g of tetrabutyl titanate and disperse it in 90.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0105] 3) Weigh 6.5 g of magnesium nitrate and disperse it in 25.9 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0106] 4) Add solution B dropwise into solution A while stirring, then place in a 35°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0107] 5) The sol obtained in step 4) is dried at 70° C. for 24 h, and then calcined at 650° C. for 2 h to obtain a magnesium titanate carrier.

[0108] 6) Ultrasonic dispersion of 8 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C. Dissolve 8.7 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 9, stir for 3 hours, and obtain a precipitate. Wash the obtained precipitate, dry it, and roast it at 550°C for 4 hours to obtain a roasted product. Reduce the roasted product with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 600°C for 5 hours to obtain 10 g of catalyst. The iron content of the catalyst in terms of iron element is 20% by weight.

[0109] Example 5

[0110] 1) Prepare a propanol-glacial acetic acid mixed solution by mixing glacial acetic acid and propanol in a mass ratio of 2:3.

[0111] 2) Weigh 24.1 g of tetrabutyl titanate and disperse it in 168.5 g of a propanol-glacial acetic acid mixed solution to obtain solution A.

[0112] 3) Weigh 6.9 g of magnesium nitrate and disperse it in 27.5 g of a propanol-glacial acetic acid mixed solution to obtain a solution B.

[0113] 4) Add solution B dropwise into solution A while stirring, then place in a 40°C water bath and let stand for 5 hours to obtain a sol with a pH of 3.8.

[0114] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0115] 6) Ultrasonic dispersion of 8.5 g of magnesium titanate obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 6.5 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 15% by weight in terms of iron element.

[0116] Example 6

[0117] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:2.

[0118] 2) Weigh 24.1 g of tetrabutyl titanate and disperse it in 240.7 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0119] 3) Weigh 6.9 g of magnesium nitrate and disperse it in 27.5 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0120] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 7.5 hours to obtain a sol with a pH of 4.7.

[0121] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0122] 6) Ultrasonic dispersion of 8.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 6.5 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 6 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 40% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 15% by weight in terms of iron element.

[0123] Example 7

[0124] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0125] 2) Weigh 18.03 g of ethyl titanate and disperse it in 72.1 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0126] 3) Weigh 6.9 g of magnesium nitrate and disperse it in 82.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0127] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0128] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0129] 6) Ultrasonic dispersion of 8.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 6.5 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 10, stir for 5 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst in terms of iron element is 15% by weight.

[0130] Example 8

[0131] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0132] 2) Weigh 24.1 g of tetrabutyl titanate and disperse it in 168.5 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0133] 3) Weigh 6.9 g of magnesium nitrate and disperse it in 137.7 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0134] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 4 hours to obtain a sol with a pH of 3.

[0135] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0136] 6) Ultrasonic dispersion of 8.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 6.5 g of ferric nitrate in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 hours to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. The iron content of the catalyst is 15% by weight in terms of iron element.

[0137] Example 9

[0138] The method of Example 2 is followed, except that in 1), glacial acetic acid and anhydrous ethanol are prepared at a mass ratio of 2:1 to obtain an anhydrous ethanol-glacial acetic acid mixed solution, so that the pH of the sol is 2. A catalyst is obtained.

[0139] Example 10

[0140] The method of Example 2 was followed, except that the water bath temperature in 4) was 55° C. to obtain a catalyst.

[0141] Embodiment 11

[0142] The method of Example 2 is followed, except that the magnesium titanate carrier is prepared by a method of the prior art, specifically comprising:

[0143] 1) Weigh 25.5 g of tetrabutyl titanate and disperse it in 65.5 g of glacial acetic acid to obtain solution A.

[0144] 2) Weigh 7.3 g of magnesium nitrate and disperse it in 65.6 g of anhydrous ethanol to obtain solution B.

[0145] 3) Add solution A dropwise into solution B while stirring, then place in a 30°C water bath and allow to stand to obtain a sol.

[0146] Comparative Example 1

[0147] The method of Example 2 is followed, except that instead of using magnesium titanate as a carrier, titanium dioxide is used as a carrier, that is:

[0148] Ultrasonic dispersion of 8.5g titanium dioxide in deionized water, heated to 40°C, to obtain a base solution; 6.5g ferric nitrate is dissolved in water to obtain a metal salt solution, the metal ion concentration of which is 0.5mol / L; the metal salt solution obtained in step 2) and a sodium hydroxide solution with a concentration of 2mol / L are added to the base solution obtained in step 1), the pH is controlled to 8, and stirred for 3h to obtain a precipitate. The precipitate obtained in step 3) is washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The iron content of the catalyst is 15% by weight in terms of iron element.

[0149] Comparative Example 2

[0150] The method of Example 2 was followed, except that in 3), instead of adding magnesium nitrate, an equal mole of barium nitrate was added to obtain 10 g of a catalyst having an iron content of 10% by weight in terms of iron element.

[0151] Test Example 1

[0152] The activity of the catalyst was evaluated at different temperatures using ammonia nitrogen gas with an ammonia concentration of 15% by volume. 1 g of 40-60 mesh catalyst and 4 g of 40-60 mesh quartz sand were mixed and loaded. The volume space velocity was 15000 mL / (g·h). The results of the reaction for 6 h are shown in Table 1.

[0153] Table 1

[0154]

[0155]

[0156] It can be seen from the results in Table 2 that, under the same reaction conditions, the application of the catalyst of the present invention in the ammonia decomposition hydrogen production reaction has a significantly higher ammonia decomposition conversion rate.

[0157] At the same time, compared with the comparative example, the example has a significantly higher ammonia decomposition conversion rate at 550° C., indicating that the catalyst of the present invention has a higher ammonia decomposition activity at low temperatures.

[0158] At the same time, at a higher space velocity, the example has a significantly higher ammonia decomposition conversion rate than the comparative example, indicating that the catalyst of the present invention has better stability.

[0159] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An iron-containing catalyst, characterized in that The catalyst comprises a magnesium titanate carrier and an iron element loaded on the magnesium titanate carrier; Wherein, based on the total weight of the catalyst, the content of iron is 5-20% by weight in terms of iron element.

2. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the iron content is 10-20% by weight in terms of iron element.

3. A method for preparing an iron-containing catalyst, the method comprising the following steps: S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A; S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B; S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5; S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier; S5. Loading the iron element on the magnesium titanate carrier.

4. The method according to claim 3, wherein: In S1, the mass ratio of the titanium source to the alcohol-glacial acetic acid mixed solution is 1:4-10; Preferably, the titanium source is a water-soluble titanium-containing compound, preferably at least one selected from tetrabutyl titanate, ethyl titanate and isopropyl titanate; Preferably, in S2, the mass ratio of the magnesium source to the alcohol-glacial acetic acid mixed solution is 1:4-20; Preferably, the magnesium source is a soluble magnesium salt, preferably at least one selected from magnesium nitrate, magnesium sulfate and magnesium chloride; Preferably, in the alcohol-glacial acetic acid mixed solution of S1 and S2, the mass ratio of glacial acetic acid to alcohol is independently 1:0.5-2; Preferably, the alcohols in S1 and S2 are each independently a C1-C5 alcohol, preferably at least one selected from methanol, ethanol and propanol.

5. The method according to claim 3, wherein: In S3, the pH of the sol is 3-5; Preferably, the treatment conditions include: temperature of 30-50°C, preferably 30-40°C; time of 0.5-10h, preferably 0.5-8h.

6. The method according to any one of claims 3 to 5, wherein: In S4, the drying conditions include: a temperature of 70-100° C. and a time of 8-48 hours; Preferably, in S4, the first calcination conditions include: a temperature of 600-1000° C. and a time of 2-6 hours.

7. The method according to any one of claims 3 to 6, wherein: In S5, the iron element is loaded on the magnesium titanate support by a coprecipitation method; Preferably, the coprecipitation method in S5 comprises: mixing an aqueous solution containing an iron compound, a suspension containing a magnesium titanate carrier and an alkaline solution to obtain a solid product, and then drying and second calcining the solid product; Preferably, the amount of the iron-containing compound is such that the iron content in the prepared catalyst is 5-20% by weight, preferably 10-20% by weight, calculated as the element, based on the total weight of the catalyst; Preferably, the reaction conditions include: temperature of 40-70°C, time of 3-8h, pH of 8-10; Preferably, the conditions for the second calcination include: a temperature of 550-780° C. and a time of 2-5 hours.

8. The method according to claim 7, wherein: The method further comprises: reducing the product of the second calcination to obtain the catalyst; Preferably, the reduction conditions include: temperature of 600-800°C and time of 1-3h; Preferably, the reduction is carried out in a reducing gas, the reducing gas comprising hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%; Preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon.

9. Use of the iron-containing catalyst according to claim 1 or 2 or the iron-containing catalyst prepared by the preparation method according to any one of claims 3 to 8 in hydrogen production by decomposing ammonia.

10. A method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions that decompose ammonia; Wherein, the catalyst is the catalyst according to claim 1 or 2 or the iron-containing catalyst prepared by the preparation method according to any one of claims 3 to 8; Preferably, the conditions for decomposing ammonia include: a temperature of 550-650° C. and a volume space velocity of 5000-20000 mL / (g·h).

Citation Information

Patent Citations

  • Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

    CN115646500A

  • Prepn and application of nickel-based catalyst for decomposing ammonia to prepare mixed H2-N2 gas

    CN1506299A

  • Application of nano magnesium titanate used as solid-phase extraction adsorption medium in heavy metal ion enrichment

    CN102218224A

  • Perovskite type catalyst for ammonia decomposition as well as preparation method and application of perovskite type catalyst

    CN114534736A

  • Nickel-based catalyst as well as preparation method and application thereof

    CN116408103A